2002
DOI: 10.1172/jci15451
|View full text |Cite
|
Sign up to set email alerts
|

Transport of paclitaxel (Taxol) across the blood-brain barrier in vitro and in vivo

Abstract: Paclitaxel concentrations in the brain are very low after intravenous injection. Since paclitaxel is excluded from some tumors by p-glycoprotein (p-gp), the same mechanism may prevent entry into the brain. In vitro, paclitaxel transport was examined in capillaries from rat brains by confocal microscopy using BODIPY Fl-paclitaxel. Western blots and immunostaining demonstrated apical expression of p-gp in isolated endothelial cells, vessels, and tissue. Secretion of BODIPY Fl-paclitaxel into capillary lumens was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
105
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(109 citation statements)
references
References 40 publications
3
105
0
1
Order By: Relevance
“…The in vivo experiments with NMRI nu/nu mice were performed as described by Fellner et al (2002). Six-to 8-week-old NMRI nu/nu mice were assigned to groups of three animals per time point.…”
Section: Chemosensitivity Assaymentioning
confidence: 99%
See 3 more Smart Citations
“…The in vivo experiments with NMRI nu/nu mice were performed as described by Fellner et al (2002). Six-to 8-week-old NMRI nu/nu mice were assigned to groups of three animals per time point.…”
Section: Chemosensitivity Assaymentioning
confidence: 99%
“…However, the efficacy of paclitaxel in the systemic treatment of these tumors is variable and low. Although paclitaxel should be able to penetrate across the bloodbrain barrier because of its physiochemical properties, its access to the brain is limited because of its high affinity to the efflux transporter ABCB1 (p-glycoprotein 170, p-gp) (Fellner et al 2002;Sparreboom et al 1997;van Asperen et al 1997). By blocking the ABCB1 mediated efflux it is possible to increase the concentration of ABCB1 substrates, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…PTX has been shown to have high therapeutic activity in GBM, if the drug can be administered efficiently, such as with convection-enhanced delivery. 13,14 Recent studies showed that coadministration of the P-gp inhibitor (valspodar) was found to enhance the brain uptake of PTX, a P-gp substrate, and improve anti-tumor therapeutic effect. 15 The short chain sphingolipids, such as ceramide, which are second messengers in the cell, have been found to play a crucial role as mediators of apoptotic signaling.…”
Section: Introductionmentioning
confidence: 99%